You are looking for two consecutive odd integers totaling -76. You would use x to represent the first integers and you would use x + 2 for the second integer since odd numbers are two spaces away from each other.
1st integer = x
2nd integer = x + 2
You would set up the equation as
x + (x + 2) = -76.
You would then simply the left side and solve for x.
x + (× + 2) = -76 (combine like terms to remove parentheses)
2x + 2 = -76 (subtract 2 from each side)
2x = -76 (divide each side by 2 to solve for x)
x = -39
1st integer: x = -39
2nd integer: x + 2
-39 + 2 = -37
-39 + -37 = -76